Ultrastructural basis for chloroquine-induced increase in intracellular insulin in adipocytes: alteration of lysosomal function. - Smith, R M (1982)
A quantitative morphological analysis of insulin uptake into adipocytes was undertaken to determine the structural basis for chloroquine-induced increases in intracellular insulin. Adipocytes were incubated with ferritin-labeled insulin in the presence or absence of 50 microM chloroquine at 37 degrees C for 2-90 min and the uptake of the hormone conjugate was determined quantitatively. Quantitative morphometry of cellular organelles also was performed. Chloroquine treatment of adipocytes incubated with 70 nM ferritin-labeled insulin resulted in: (i) a 120% increase in the number of lysosomes in the cytoplasm; (ii) a 75% increase in the average concentration of ferritin-labeled insulin in a lysosome; and (iii) a 25% increase in the percentage of lysosomes containing ferritin-labeled insulin. The cumulative result of these effects was a substantial increase in the amount of intact intracellular hormone within the lysosomes. These morphological data are consistent with biochemical data concerning chloroquine-induced accumulation of 125I-labeled insulin in adipocytes.